Viral, bacterial, and fungal infections of the oral mucosa: Types, incidence, predisposing factors, diagnostic algorithms, and management. Issue 1 (15th May 2019) - Bandara, H. M. H. N.; Samaranayake, Lakshman P.
Abstract: For millions of years, microbiota residing within us, including those in the oral cavity, coexisted in a harmonious symbiotic fashion that provided a quintessential foundation for human health. It is now clear that disruption of such a healthy relationship leading to microbial dysbiosis causes a wide array of infections, ranging from localized, mild, superficial infections to deep, disseminated life‐threatening diseases. With recent advances in research, diagnostics, and improved surveillance we are witnessing an array of emerging and re‐emerging oral infections and orofacial manifestations of systemic infections. Orofacial infections may cause significant discomfort to the patients and unnecessary economic burden. Thus, the early recognition of such infections is paramount for holistic patient management, and oral clinicians have a critical role in recognizing, diagnosing, managing, and preventing either new or old orofacial infections. This paper aims to provide an update on current understanding of well‐established and emerging viral, bacterial, and fungal infections manifesting in the human oral cavity.